Harvesting solar energy for UAV - Poh, Wen Jie (2015)
Quadcopters are unmanned helicopters lifted by 4 rotors. They come in many sizes and used in a wide range of applications from the military to commercial sector. LiPo (Lithium polymer) batteries are typically used to run these quadcopters. Recharging the depleted batteries is a hassle when flying the quadcopters outdoor as power sources are not available. An alternative source of power would be solar energy. The aim of this project is to explore means to harvest solar energy to charge the quadcopter battery. Supercapacitors are used to store the energy that are collected by solar cell. Energy stored are used to charge the battery using a wireless charging module as the quadcopters land. Additonal solar cells are added to investigate the effects of charging the LiPo battery. A solar LiPo charger was also used to charge the LiPo battery. The readings of the battery voltage are recorded at intervals.